2020
DOI: 10.1111/jfpp.14795
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of tea varieties based on FTIR spectroscopy and an adaptive improved possibilistic c‐means clustering

Abstract: As a green and healthy beverage, tea has been fascinated by the people

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
2
6
0
Order By: Relevance
“…For a number of compounds, including carboxylic acids, esters, and alcohols, a sharp and strong peak lies at 1036 cm −1 ; identifying the stretching modes of C-O and the stretching vibration peaks around1236 cm −1 originates from the C-N vibrations in aliphatic amine groups [ 39 , 40 ]. The recorded FTIR spectra in the present study for BTLs is relatively analogous to those reported in the literature for green and black teas [ 33 , 36 , 41 , 42 , 43 , 44 , 45 ]. Both the bending and stretching vibrations in pyrimidine, imidazole, carbonyl, and methyl groups are in good accordance with the bands in the caffeine spectra that change between 1700 cm −1 and 400 cm −1 [ 46 , 47 , 48 ].…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…For a number of compounds, including carboxylic acids, esters, and alcohols, a sharp and strong peak lies at 1036 cm −1 ; identifying the stretching modes of C-O and the stretching vibration peaks around1236 cm −1 originates from the C-N vibrations in aliphatic amine groups [ 39 , 40 ]. The recorded FTIR spectra in the present study for BTLs is relatively analogous to those reported in the literature for green and black teas [ 33 , 36 , 41 , 42 , 43 , 44 , 45 ]. Both the bending and stretching vibrations in pyrimidine, imidazole, carbonyl, and methyl groups are in good accordance with the bands in the caffeine spectra that change between 1700 cm −1 and 400 cm −1 [ 46 , 47 , 48 ].…”
Section: Resultssupporting
confidence: 81%
“…The functional groups of the BTL sample could be obtained by analyzing the spectral range between 400 and 4000 cm −1 , since it allows for the identification of the vibrational frequency of the chemical bonds that make up both inorganic and organic molecules. Absorption at functional groups occurs as a result of vibrations in a certain frequency band and exhibits a clear feature of IR absorption [ 33 ]. Figure 4 displays the FTIR spectra of BTL extracts.…”
Section: Resultsmentioning
confidence: 99%
“…With the help of multivariate calibration methods such as partial least squares (PLS) algorithm, random frog (RF) crossed with PLS (RF‐PLS), and competitive adaptive reweighted sampling (CARS) crossed with PLS (CARS‐PLS), FT‐NIR has been widely applied in simultaneously quantifying the levels of catechins, caffeine, free amino acids, theaflavins, and moisture in tea leaves or final tea products (Chen et al., 2008; Chen, Zhao, Chaitep et al., 2009; Wang, Wang et al., 2018; Zareef et al., 2018). Besides, FT‐NIR and FT‐MIR coupled with pattern recognition methods can also be widely used to discriminate teas with different varieties and geographical origins, and even can be applied in identifying tea grades and tea processing degree, such as the fermentation degree of black teas (Chen et al., 2009; Esteki et al., 2022; Jin et al., 2020; Song et al., 2021; Zhou, Fu et al., 2020). Unlike MS based metabolomics, FT‐IR based metabolomics is more suitable for discriminant analysis of tea samples rather than searching for marker compounds due to the heavily overlapped peaks in the FT‐IR spectra of tea samples.…”
Section: Applications Of Metabolomics In Tea Studiesmentioning
confidence: 99%
“…significantly increased after rocking process, and some of them escaped into the air (Hu et al., 2018; Liu et al., 2018). These volatiles are derived from phenylalanine, long‐chain fatty acids ( e.g ., α‐linolenic acid and linoleic acid), carotenoids, and glycosidically bound volatiles (GBVs), or from de novo synthesis (Hu et al., 2018; Zhou, Wu et al., 2020). However, many years of studies by Ziyin Yang's group have demonstrated that GBVs contributed less to forming free volatiles during the rocking process.…”
Section: Applications Of Metabolomics In Tea Studiesmentioning
confidence: 99%
“…Thus, there is a growing need for methods that can differentiate tea products. In fact, many analytical methods have been explored for tea discrimination, which include high-performance liquid chromatography (HPLC), , gas chromatography–mass spectrometry (GC–MS), inductively coupled plasma mass spectrometry (ICP-MS), colorimetric assay and fluorometric sensors, Fourier transform infrared reflectance (FTIR) spectroscopy, , and nuclear magnetic resonance (NMR) spectroscopy . These techniques are reliable but tend to be time consuming.…”
Section: Introductionmentioning
confidence: 99%